Thermal performance enhancement of solar collectors by nanoparticles and magnetic field: a review - Norhan Dawood; Jalal Jalil; Sahar Faraj (Engineering and Technology Journal)
The implementation of nanoparticles in solar thermal conversion devices has long been a challenge. Consequently, employing ferrofluids combined with magnetic fields has been an intriguing investigation. The magnetization of magnetic nanoparticles, which noticeably enhances the thermal conductivity of ferrofluid, is one of the principal effects of the magnetic field. Given that the compelling behavior of ferrofluid in the presence of external magnetic fields supplied by either permanent magnets or current-carrying wire as the primary source of magnetic field and the significant effect of this combination on the thermal performance of solar devices, the current review focused on introducing research involving various collections of nanoparticles, ranging from solid metal to metal oxide and hybrid nanoparticles, and demonstrating their effect on the thermal conductivity. Based on the literature, results indicated that in particular cases, by applying a magnetic field in the range of 0.02-1T via permanent magnet and in the presence of hybrid nanoparticles Mn-Zn  for 0.5 vol%, the highest improvement in the obtained efficiency of the thermal is about 47%. Contemporary, the best performance of 74% was obtained for 4 vol% of Therminol 66 ferrofluid under a 500 G magnetic field supplied by current carrying wire.